A comparison between a refined two-point model for the limited tokamak SOL and self-consistent plasma turbulence simulations. (6th March 2017) - Wersal, C; Ricci, P; Loizu, J
Abstract: A refined two-point model is derived from the drift-reduced Braginskii equations for the limited tokamak scrape-off layer (SOL) by balancing the parallel and perpendicular transport of plasma and heat and taking into account the plasma–neutral interaction. The model estimates the electron temperature drop along a field line, from a region far from the limiter to the limiter plates. Self-consistent first-principles turbulence simulations of the SOL plasma including its interaction with neutral atoms are performed with the GBS code and compared to the refined two-point model. The refined two-point model is shown to be in very good agreement with the turbulence simulation results.